An emergent European executive order - Trondal, Jarle (Oxford : Oxford University Press, 2010)
The book examines how the European Union profoundly penetrates the domestic branch of executive government. The author explores the accumulated organisational capacities and the every-day decision-making dynamics inside three key institutions: the European Commission, EU-level agencies, and EU committees.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union; European Commission; European Union countries -- Politics and government